Pelatihan Pengolahan Makanan Pagi (Breakfast) Bagi Pelaku Wisata di Nusa Lembongan, Bali - Ni Putu Eka Trisdayanti; I Gusti Made Iwan Dusanta Martadjaya; I Made Hendrayana (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2022)
The opening of Bali for foreign tourists certainly requires great preparation, due to the large number of tourism accommodations that have been closed for a long time and also the preparation of human resources considering that it has been almost 2 years not serving tourists due to the Covid-19 Pandemic. Based on this, a short training program in the form of breakfast processing training activities for tourism actors in Nusa Lembongan was carried out. This activity aims to remind and improve the skills of tourism actors, especially in the culinary field. The method used in this training session is the presentation of theories on the application of hygiene and sanitation in food processing, restaurant/restaurant CHSE, menu knowledge, cooking demonstrations, and hands-on practice from the participants. The results of the evaluation showed that the participants were enthusiastic about participating in the training and were able to practice food processing methods